Financial and Institutional Support Are Important for Large-Scale Kelp Forest Restoration - Eger, Aaron M.; Vergés, Adriana; Choi, Chang Geun; Christie, Hartvig; Coleman, Melinda A.; Fagerli, Camilla W.; Fujita, Daisuke; Hasegawa, Masatoshi; Kim, Jeong Ha; Mayer-Pinto, Mariana; Reed, Dan C.; Steinberg, Peter D.; et al. (Frontiers in Marine Science, 2020)
Kelps form extensive underwater forests that underpin valuable ecosystem goods and services in temperate and polar rocky coastlines globally. Stressors such as ocean warming and pollution are causing regional declines of kelp forests and their associated services worldwide. Kelp forest restoration is becoming a prominent management intervention, but we have little understanding of what drives restoration success at appropriate spatial scales. Though most restoration guidelines stress the importance of planning, stressor mitigation and ecological knowledge, other factors such as lack of resources or institutional support are rarely discussed despite being potentially critical to achieving desired restoration outcomes. In this paper, we work to understand the importance of finances and institutions in the context of four of the world’s largest kelp restoration projects. These projects span four countries, six kelp genera and were initiated in response to different causes of decline. We argue that to restore kelp at desired scales, adequate financing and institutional support are critical to overcome ecological and environmental limitations. Acknowledging limitations, we outline ways to mobilize resources and encourage institutions to support kelp restoration.